SYST-01 MULTI-INSTITUTIONAL RANDOMIZED TRIAL COMPARING CANCER STEM CELL-TARGETED VS PHYSICIAN-CHOICE TREATMENTS IN PATIENTS WITH RECURRENT HIGH-GRADE GLIOMAS (NCT03632135). (5th August 2022) - Sengupta, Soma; Ranjan, Tulika; Yu, Alexander; Howard, Candace; Chen, Ricky; Chaudahary, Rekha; Marko, Nicholas; Aregawi, Darit; Glantz, Michael; Glass, Jon; Green, Richard; Lu-Hemerson, Christine; et al.
Abstract: BACKGROUND: Clinical outcomes in patients with recurrent high-grade glioma (HGG) remain poor. Cancer stem cells (CSCs) have been implicated in metastasis, treatment resistance and recurrence of HHGs. We have shown in several clinical studies that anti-CSC-directed therapy provides benefits in many cancer types; however, this is the first report of a randomized clinical trial evaluating it for recurrent HGGs. OBJECTIVE: Determine whether CSC-targeted cytotoxic agents selected by ChemoID assay-guided therapy improves survival in patients with recurrent HGG. DESIGN, SETTING, AND PARTICIPANTS: In this parallel-group, randomized, phase-3 clinical trial, patients at 13 clinical sites in the USA with grade-III/IV recurrent glioma (2016 WHO guidelines) were randomized 1:1 to either ChemoID assay-guided therapy or physician-choice therapy, and then treated and followed until unacceptable toxic effects, hospice, or death. MAIN OUTCOMES AND MEASURES: The primary endpoint was overall survival (OS). RESULTS: Combined median follow-up was 9 months. Median OS (mOS) was 12.5 months (95% CI, 10.2-14.7) in the ChemoID assay-guided group vs 9 months (95% CI, 4.2-13.8) in the physician-choice group (log-rank P = .010). Risk of death was significantly lower in the ChemoID assay group (HR = 0.44; 95% CI, 0.24-0.81; P = .008). Median progression free survival (PFS) was 10.1 vs 3.5 months (95% CI, 4.8-15.4 vs 1.9-5.1) (HR, 0.25; 95% CI, 0.14-0.44; P < .001). CONCLUSIONS AND RELEVANCE: Primary endpoint was met in this randomized clinical trial. The mOS was 3.5 months longer in the ChemoID assay-guided group vs the physician-choice group.